KIBARAN GRANITOID MAGMATISM IN THE REPUBLIC OF BURUNDI: GEOLOGY, COMPOSITIONAL FEATURES, TIME AND GEODYNAMIC CONDITIONS OF OCCURRENCE - V. M. Nenakhov; B. Barihuta; V. V. Ilin (Геодинамика и тектонофизика, 2024)
The paper examines the specific granitoid magmatism of the northern sector of the Kibaran orogenic belt in the general context of geodynamic typification of granitoids. It presents parameters and main features of the structure with an emphasis on the sectorial nature of the belt typical of intraplate settings and shows the geological features of the eastern and western blocks of the northern sector. The paper provides general information on S- and A-type granitoids and a description of the geological position and macrofeatures of "reference" massifs. The petrochemical characteristics of S- and A-granitoids are given using various diagrams. Analysis of geochronological database available to date (including Rb-Sr isochron age of rocks and SHRIMP U-Pb age of zircons) shows the multi-pulse nature of the manifestation of intraplate granite formation. Along with the main stages (~1375, ~1205, ~986 Ma), there are five others. Based on the total dataset, S-type granitoids in Burundi are characterized by the crust-mantle interaction signs which are somewhat contrary to the generally accepted opinion that they are purely crustal. At the same time, some varieties of A-type granitoids are characterized by corundonormativity which makes them more similar to the S-type. Thus, signs of convergence between S- and A-granites are characteristic of some intraplate environments such as "hot spots", primarily of those longlived and multi-pulse, with the relevant protolith represented by a complex of sediments with high exogenous differentiation. One of the version of the granite formation model is illustrated by the corresponding figure.